Vavouranakis, G., Kopanias, K., Kanellopoulos, C. (eds.) (2018). Popular Religion and Ritual in Prehistoric and Ancient Greece and the Eastern Mediterranean - Cusumano, Nicola (ARYS. Antigüedad: Religiones y Sociedades, 2020)
VAVOURANAKIS, GIORGOS, KOPANIAS, KONSTANTINOS, and KANELLOPOULOS, CHRYSANTHOS (eds.) (2018). Popular Religion and Ritual in Prehistoric and Ancient Greece and the Eastern Mediterranean. Oxford: Archaeopress. 188 pp., 38,40€ [ISBN 978-1-7896-9045-3] [Book review]